Perlindungan Hukum Terhadap Korban Kekerasan dalam Rumah Tangga: Penelitian - Nurliana Ritonga; Dormada Lestari Luhur Sitorus; Arum Tsabitah S.; Cahaya Mutiara; Rina Rouli Br. Hutagaol; Khairul Akmal Panjaitan; Dinda Agustin Situmorang (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Legal protection for victims of Domestic Violence (KDRT) is a crucial step in shifting the community paradigm from a domestic issue to a public concern. This activity aims to increase the legal awareness of the Sei Alim Hasak Village community regarding victims' rights, forms of violence, and protection mechanisms regulated in Law No. 23 of 2004. The implementation methods include material presentations, interactive discussions, and legal consultation sessions. The results show an increase in community understanding and the growth of collective awareness to prioritize the welfare and safety of residents. Synergy between academics, village officials, and the community is a key factor in the effectiveness of this program to create a harmonious family environment free from violence.